Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
Bài 1:
\(a,\left(a+b-c\right)-\left(b-c-d\right)\)
\(=a+b-c-b+c+d\)
\(=a+d\)
\(b,-\left(a-b+c\right)+\left(a-b+d\right)\)
\(=-a+b-c+a-b+d\)
\(=-c+d\)
\(c,\left(a+b\right)-\left(-a+b-c\right)\)
\(=a+b+a-b+c\)
\(=2a+c\)
\(d,-\left(a+b\right)+\left(a+b+c\right)\)
\(=-a-b+a+b+c\)
\(=c\)
Bài 3 :
\(a,15-\left(4-x\right)=6\)
\(4-x=15-6\)
\(4-x=9\)
\(x=4-9\)
\(x=-5\)
\(b,-30+\left(25-x\right)=-1\)
\(25-x=-1+30\)
\(25-x=29\)
\(x=25-29\)
\(x=-4\)
\(c,x-5=-1\)
\(x=-1+5\)
\(x=4\)
\(d,x-4=-10\)
\(x=-10+4\)
\(x=-6\)
\(e,x+3=-8\)
\(x=-8-3\)
\(x=-11\)
\(g,x+6=0\)
\(x=-6\)
Câu 1:
A, (a+b-c)-(b-c-d)
= a+b-c-b+c+d
= a+(b-b)+(c-c)
= a
B, -(a-b+c)+(a-b+d)
= -a+b-c+a+b+d
= (a-a)+(b+b)+d-c
= 2b+d-c
C, (a+b)-(-a+b-c)
= a+b+a-b+c
= (a+a)+(b-b)+c
= 2a+c
D, -(a+b)+(a+b+c)
= -a-b+a+b+c
= (-a+a)+(b-b)+c
= c
=
![](https://rs.olm.vn/images/avt/0.png?1311)
Bài 1:
a)
<=> 3x - 18 - 5x + 10 = 24
<=> 3x - 5x = 24 + 18 - 10
<=> -2x = 32
<=> x = 32 : (-2)
<=> x = -16
b)
<=> -4x + 20 - 8x + 16 = 48
<=> -4x - 8x = 48 - 20 - 16
<=> -12x = 12
<=> x = 12 : (-12)
<=> x = -1
Bài 2:
\(=a^2-ab+ab-b^2\)
\(=a^2-b^2\)
a) 3(x-6)-5(x-2) = 24
<=> 3x -36 -5x + 10 =24
<=> -2x = 50
<=> x = -25
b) -4(x-5) -8(x-2) = 48
<=> -4x +20 - 8x +16 = 48
<=> -12x = 12
<=> x = -1
(a+b)(a-b) = a^2 -ab +ab -b^2 = a^2 - b^2
![](https://rs.olm.vn/images/avt/0.png?1311)
Bài 1: tính nhanh
a. 579 + 468 + 421 - 467
= (579 + 421) + (468 - 467)
= 1000 + 1
= 1001
b. 53 . 39 + 47 . 39 - 53 . 21 - 47 . 21
= 39 (53 + 47 ) - 21 (53 - 47)
= 39 . 100 - 21 . 6 = 3900 -126
= 3774
![](https://rs.olm.vn/images/avt/0.png?1311)
Bài 2:
\(x^5=x^3\)
\(\Rightarrow x^5-x^3=0\)
\(\Rightarrow x^3\left(x^2-1\right)=0\)
\(\Rightarrow x^3=0\) hoặc \(x^2-1=0\)
+) \(x^3=0\Rightarrow x=0\)
+) \(x^2-1=0\Rightarrow x^2=1\Rightarrow x=1\) hoặc \(x=-1\)
Vậy \(x\in\left\{0;1;-1\right\}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(27-\left(14-x\right)=-x+3\)
\(\Leftrightarrow\)\(27-14+x=-x+3\)
\(\Leftrightarrow\)\(13+x=-x+3\)
\(\Leftrightarrow\)\(2x=-10\)
\(\Leftrightarrow\)\(x=-5\)
Vậy...
Câu 1 :
=> 27-14+x = -x+3
=> 13+x = -x+3
=> x = -x+3-13 = -x-10
=> 10 = -x-x = -2x
=> x = 10 : (-2) = -5
Vậy x = -5
Tk mk nha
a) 3|x - 1| = |-27|
=> 3|x - 1| = 27
=> |x - 1| = 27 : 3
=> |x - 1| = 9
TH1: x - 1 = 9
=> x = 9 + 1
=> x = 10
TH2: x - 1 = -9
=> x = -9 + 1
=> x = -8
Vậy x = 10 hoặc x = -8
a) 3 * | x - 1 | = | -27 |
=> 3 * | x - 1 | = 27
=> | x - 1 | = 27 : 3
=> | x - 1 | = 9
\(=>\hept{\begin{cases}x-1=9\\x-1=-9\end{cases}}\)
\(=>\hept{\begin{cases}x=9+1\\x=-9+1\end{cases}}\)
\(=>\hept{\begin{cases}x=10\\x=-8\end{cases}}\)
b) -6 * x - 14 = -44
=> -6 * x = -44 + 14
=> -6 * x = -30
=> x = -30 : -6
=> x = 5
c) 40 - ( 18 + x ) = 2
=> 18 + x = 40 - 2
=> 18 + x = 38
=> x = 38 - 18
=> x = 20
d) 6 * | x | = 48
=> | x | = 48 : 6
=> | x | = 8
\(=>\hept{\begin{cases}x=8\\x=-8\end{cases}}\)